Examining links between abusive supervision, PsyCap, LMX and outcomes. Issue 5 (12th October 2018) - Agarwal, Upasna A.
Abstract : Purpose: The purpose of this paper is to propose a moderated mediation model wherein abusive supervision predicts subordinate's stress and turnover intentions through Psychological Capital (PsyCap). Leader–member exchange (LMX) moderates the abusive supervision-outcome relationship through PsyCap. Design/methodology/approach: Two wave data were collected from 1, 193 full-time employees across organizations in India. Findings: Results suggest that abusive supervision is significantly related to intention to quit and perceive stress, and this relationship is partially mediated by PsyCap. The findings from the moderated mediation analysis revealed that the mediation of PsyCap was moderated by LMX such that at the higher levels of LMX, the mediation effect of PsyCap on workout comes became stronger. Research limitations/implications: As the study did not cover all sectors, the results of this study should be interpreted with caution. Originality/value: Embedded in the conservation of resources theory, this study adds to the knowledge of how abusive supervision and LMX jointly affect PsyCap, turnover intentions and perceived stress. The results of this study indicate that abusive supervision exerts its influence on work-related outcomes and highlights the importance of taking the quality of relationship (LMX) with supervisor and personal resources into consideration when making sense of the influence of abusive supervision with employee outcomes. The study extends the current research stream of abusive supervision research to one of the underrepresented developing Asian countries, India.